Juvenile Idiopathic Arthritis Onset in a Neonate: A Rare Case Report - Abdolreza Malek; Mohammad-Saeed Sasan; Narges Afzali; Somayeh Ghahremani; Sara Ghahremani (Mashhad University of Medical Sciences, 2017)
Background: A common type of chronic arthritis in children and adolescents is juvenile idiopathic arthritis (JIA).According to the International League of Associations for Rheumatology (ILAR) classification, JIA diagnostic criteria include age under 16 years and disease duration of six-weeks. Based on the number of involved joints in the first sixmonths of disease onset, JIA is categorized into oligoarticular or polyarticular subtypes. Age is a characteristic factor in the diagnosis of disease subsets; it is worth mentioning that cases younger than six months of age are seldom found in any of the subtypes. Case report: In this report, we present a rare case of JIA in an infant, presenting at 20 days of age. Effusion of the right hip joint was one of the primary manifestations of the disease. During hospitalization, she went through sepsis workup and a four-week antibiotic therapy for management of lower limb pseudoparalysis. In spite of antibiotic therapy, she developed effusion of a second joint. According to the course and duration of symptoms and ILAR classification forJIA, oligoarticular JIA was diagnosed and treated.Conclusion: In this case, infectious diseases, such as tuberculosis and brucellosis, and malignancies were ruled out as a cause of inflammation through bone marrow aspiration, culture, and tests; ultrasound and magnetic resonance imaging showed no lytic and sclerotic lesions or a fracture. Our experience showed a rare case of JIA and suggested that JIA must be considered in children with joint inflammation at any age